2014
DOI: 10.1002/jemt.22360
|View full text |Cite
|
Sign up to set email alerts
|

Morphological changes produced by acid dissolution in Er:YAG laser irradiated dental enamel

Abstract: Several scientific reports have shown the effects of Er:YAG laser irradiation on enamel morphology. However, there is lack of information regarding the morphological alterations produced by the acid attack on the irradiated surfaces. The aim of this study was to evaluate the morphological changes produced by acid dissolution in Er:YAG laser irradiated dental enamel. Forty-eight enamel samples were divided into four groups (n = 12). GI (control); Groups II, III, and IV were irradiated with Er:YAG at 100 mJ (12.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 25 publications
1
5
0
Order By: Relevance
“…Demineralized enamel and dentin have low mechanical properties, and they are more prone to wear and abrasion. This agrees with a study by Díaz-Monroy et al [ 15 ] who reported that the dissolution rate of enamel decreases with the treatment of the enamel with fluorine or zinc ions, with the dissolution of enamel surfaces being imminent after a period. Another study analyzed the morphological changes produced by acid dissolution of the enamel irradiated with laser, considering that morphological modifications can vary depending on the unwanted effects induced by laser irradiation.…”
Section: Discussionsupporting
confidence: 93%
“…Demineralized enamel and dentin have low mechanical properties, and they are more prone to wear and abrasion. This agrees with a study by Díaz-Monroy et al [ 15 ] who reported that the dissolution rate of enamel decreases with the treatment of the enamel with fluorine or zinc ions, with the dissolution of enamel surfaces being imminent after a period. Another study analyzed the morphological changes produced by acid dissolution of the enamel irradiated with laser, considering that morphological modifications can vary depending on the unwanted effects induced by laser irradiation.…”
Section: Discussionsupporting
confidence: 93%
“…For XP Bond adhesive, the phosphoric acid etching may cause the detachment of more ablated dentinal structures, which were seen incorporated by the adhesive layer (Figure 3c-f). On the other hand, the acid etching applied to ablated dentin was not able to remove the peritubular dentin (Figure 3c,e,f), because the alterations promoted by the Er:YAG laser on the mineral content may have created resistance against acid attack (Bevilácqua et al, 2008;Díaz-Monroy et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Zamudio-Ortega et al [11] reported morphological changes from mild to severe on Er:YAG laser irradiated enamel of primary teeth, according to the employed energy densities and applied protocol, and concluded that the Er:YAG energy density influenced chemical changes in the enamel to enhance its structural mineral content. Furthermore, irradiation effects such as exposed enamel prisms, rough surfaces, craters, fractures, melting, recrystallization, or even carbonization have been reported by several authors [11,19].…”
Section: Introductionmentioning
confidence: 96%
“…In the dental literature, there are many studies about the effects of different local and general factors on the human dental enamel microstructure such as: age-related changes [1], the consumption of various beverages [2][3][4][5], toothpastes [6][7][8], toothbrushing [5,8,9], fluoride [10,11], bleaching [12][13][14][15], conventional etching [16], laser etching [17], laser irradiation [11,[18][19][20], biological factors such as saliva and acquired pellicle [9,21], developmental defects of the enamel [22][23][24][25],…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation